Room Temperature Ferromagnetism: Nonmagnetic Semiconductor Oxides and Nonmagnetic Dopants - Yakout, Saad Mabrouk (Journal of electronic materials, 2021)
Advances in room temperature ferromagnetic semiconductors increase the opportunity to commercialize full spintronic devices. The manipulation of electron spin in semiconductor materials has driven significant research activity with the goal of realizing their amazing technological potential. Coupling of magnetic and semiconducting properties could lead to a new generation of information and communication devices. During the past 20 years, the intensive research on magnetic semiconductor materials has led to discovery of two interesting facts. Room temperature ferromagnetism is observed in undoped semiconductor oxides with empty or completely filled d- or f-orbitals, and nonmagnetic dopants can induce or enhance the room temperature ferromagnetism in nonmagnetic semiconductor materials. The organized review which addresses this phenomenon and covers the large number of studies on this subject is rare. In this study, we firstly review the advantages aspects of spintronic devices as well as the materials suitable for these applications. Here, we tried to provide a systematic study on defects induced by room temperature ferromagnetism in undoped semiconductor oxides as well as the impact of nonmagnetic dopants on ferromagnetism. We hope this review assist researchers in creating a complete picture to develop future research activities to access innovative technological applications.